EWOA-OPF: Effective Whale Optimization Algorithm to Solve Optimal Power Flow Problem; Electronics; Vol. 10, iss. 23 - Nadimi-Shahraki M. H. Mohammad; Taghian S. Shokooh; Mirjalili S. Seyedali; Abualigah L. Laith; Mokhamed Elsaed (Mohamed Abd Elaziz) A. M. Akhmed Mokhamed; Oliva Navarro D. A. Diego Alberto (2021, 2021)
Title screen